Corpus Literacy and Applications in Norwegian Upper Secondary Schools: Teacher and Learner Perspectives - Hagen Karlsen , Petter; Monsen, Marte (Nordic Journal of English Studies, 2020)
This study explores corpus literacy and pedagogical corpus applications among in-service teachers who have corpus linguistics in their educational background, along with their students of English in upper secondary school in Norway. In order to investigate the multifaceted nature of educational practice, the study took a wide perspective encompassing aspects of digitalization in education, general pedagogy, and corpus linguistics. The students (n=154) answered an online questionnaire and four teachers were interviewed. The data are discussed in light of a technology integration framework that takes into account teacher knowledge, resource availability, teacher beliefs, as well as student epistemologies. Findings show little to no corpus literacy among the students, with the exception of one student. The interviews show that the teachers have largely avoided corpora in their teaching practice. One reason why the teachers chose to do so was due to inaccessibility related to paywalls, registration requirements and functionality restrictions. Other potential reasons that were uncovered were tied to their perception of learner competencies, how the affordances of corpora fit their curricular focus, and how their epistemic beliefs about language learning influenced their choices.